Dietary exposure to endocrine disrupting chemicals in metropolitan population from China: A risk assessment based on probabilistic approach. (November 2015) - He, Dongliang; Ye, Xiaolei; Xiao, Yonghua; Zhao, Nana; Long, Jia; Zhang, Piwei; Fan, Ying; Ding, Shibin; Jin, Xin; Tian, Chong; Xu, Shunqing; Ying, Chenjiang
Highlights: Seven out of eight EDCs were detected in most raw and fresh food in China. NP, EE2, and BPA coexisted in food. Human exposure to NP, EE2 and BPA was far below TDI. ΣEEQs exposure in population was considerably higher than E2 . The risk of co-exposure to multiple EDCs should not be ignored. Abstract: The intake of contaminated foods is an important exposure pathway for endocrine disrupting chemicals (EDCs). However, data on the occurrence of EDCs in foodstuffs are sporadic and the resultant risk of co-exposure is rarely concerned. In this study, 450 food samples representing 7 food categories (mainly raw and fresh food), collected from three geographic cities in China, were analyzed for eight EDCs using high performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS). Besides estrone (E1 ), other EDCs including diethylstilbestrol (DES), nonylphenol (NP), bisphenol A (BPA), octylphenol (OP), 17β-estradiol (E2 ), 17α-ethinylestradiol (EE2 ), and estriol (E3 ) were ubiquitous in food. Dose-dependent relationships were found between NP and EE2 ( r = 0.196, p < 0.05), BPA ( r = 0.391, p < 0.05). Moreover, there existed a correspondence between EDCs congener and food category. Based on the obtained database of EDCs concentration combined with local food consumption, dietary EDCs exposure was estimated using the Monte Carlo Risk Assessment (MCRA) system. The 50th and 95th percentile exposure of any EDCs isomer were far below the tolerable daily intake (TDI) value identically. However, the sum of 17β-estradiol equivalents (∑EEQs) exposure in population was considerably larger than the value of exposure to E2, which implied the underlying resultant risk of multiple EDCs in food should be concern. In conclusion, co-exposure via food consumption should be considered rather than individual EDCs during health risk evaluation.